Interaction between Religious Communities of Klaipėda City and Soviet Authority in 1945–1954 - Grikšaitė, Inesa (Genocidas ir rezistencija, 2007)
The purpose of this work is to describe the life conditions of religious communities and Soviet authority’s fighting against ecclesiastical institutions in 1945–1954 year in Klaipėda. The research is based on official documents, periodical press and memoirs of people were used. After the World War II Klaipėda was rebuilt, demographic situation had changed, the city was repopulated. Traditional, as well as new religions emerged the city were trying to get places for their activities and a right to execute rituals, the same time Soviet regime continued the policy of atheism. Soviet authority was trying to create the typical soviet atmosphere in Klaipėda, but it wasn’t able to stop the development of religious communities.